Response surface methodological (RSM) approach for optimizing the mechanical properties of starch-based films incorporated with chitosan-encapsulated thymol - Ahmad Shapi’i, Ruzanna; Othman, Siti Hajar; Naim, Mohd Nazli; Mohamed Amin Tawakkal, Intan Syafinaz; Mohd Basri, Mohd Salahuddin (Institute of Physics, 2025)
In this study, starch-based films incorporated with glycerol and chitosan-encapsulated thymol (CNP-T) were formulated for potential active packaging applications. The central composite design (CCD) technique was used to formulate the films and 42 runs were generated based on three replications on two factors at five levels, particularly the concentration of glycerol (V1: 0, 6.25, 12.5, 18.75, 25% wt/wt of starch) and concentration of CNP-T (V2: 0, 0.2, 0.4, 0.6, 0.8% wt/v of starch). The optimized values for V1 and V2 were found to be 25% wt/wt and 0.8% wt/v, respectively, whereby the predicted values of the tensile strength (TS) and elongation at break (EAB) were 17.40 MPa and 40.01%, respectively. The optimized formulation offers a promising foundation for producing starch-based films containing CNP-T with enhanced mechanical properties, suitable for sustainable active packaging applications in the food industry.